1997
DOI: 10.1007/s002130050287
|View full text |Cite
|
Sign up to set email alerts
|

The continuous and simultaneous blood flow velocity measurement of four cerebral vessels and a peripheral vessel during cigarette smoking

Abstract: There has been no consensus about the acute effect of cigarette smoking on cerebral blood flow, and the continuous change of flow in four cerebral vessel flow with peripheral flow during different kinds of cigarette smoking has not been reported until now. Our results indicate smoking increases the flow of four cerebral vessels almost at the same time and with the same pattern. Many cerebral vessels began to show increases about 10 s after commencement. In most cases, cerebral blood velocity began to decrease … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
1
1

Year Published

2001
2001
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 19 publications
(31 reference statements)
1
11
1
1
Order By: Relevance
“…However, observations on the effects of cigarette smoking on the cerebral vasculature conflict with each other, with some investigators reporting increases (Kodaira et al, 1993) and others reporting decreases in cerebral blood flow lasting during smoking and 5 min after smoking (Cruickshank et al, 1989;Morioka et al, 1997). More importantly, however, our analysis of covariance revealed that the number of years that the subjects smoked did not influence the PI results.…”
Section: Discussioncontrasting
confidence: 54%
See 1 more Smart Citation
“…However, observations on the effects of cigarette smoking on the cerebral vasculature conflict with each other, with some investigators reporting increases (Kodaira et al, 1993) and others reporting decreases in cerebral blood flow lasting during smoking and 5 min after smoking (Cruickshank et al, 1989;Morioka et al, 1997). More importantly, however, our analysis of covariance revealed that the number of years that the subjects smoked did not influence the PI results.…”
Section: Discussioncontrasting
confidence: 54%
“…It is also possible to suggest that these difference in flow resistance are attributable to cigarette smoking because smoking has been reported to cause acute changes in vascular flow (Cruickshank et al, 1989;Kodaira et al, 1993;Morioka et al, 1997). However, observations on the effects of cigarette smoking on the cerebral vasculature conflict with each other, with some investigators reporting increases (Kodaira et al, 1993) and others reporting decreases in cerebral blood flow lasting during smoking and 5 min after smoking (Cruickshank et al, 1989;Morioka et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Previous transcranial Doppler sonography studies of the acute effects of smoking on cerebral vasculature have shown an increase in cerebral blood flow velocity and a reduction in PI, CO2 reactivity and breathholding index. 5,21,22 Other cerebral blood flow studies have demonstrated a chronic decrease in regional cerebral blood flow and quitting smoking has been shown to increase it. 23,24 Liang et al reported that there was an increased stiffness index in the carotid artery of middle-aged and elderly smokers compared with nonsmokers, 25 and Kool et al showed an acute decrease in the distensibility of both the elastic CCA and the muscular brachial artery.…”
Section: Discussionmentioning
confidence: 99%
“…The study by Ghatan et al [18] showed a nicotine-induced CBF decrease in the anterior cingulate cortex and the cerebellum, and a concomitant increase in the occipital cortex in smokers and nonsmokers. Smoking increases the flow of four cerebral vessels, but decreases in peripheral vessels after commencement, which is thought to be the effect of nicotine [19] . In a transcranial Doppler study by Boyajian and Otis [20] , smoking acutely increased flow in median cerebral artery.…”
Section: Discussionmentioning
confidence: 99%